The Effect of Using Exercises With Aids for Teaching Types of Shooting To Sophomore Students - Mohameed, Alaa (Journal of Physical Education, 2017)
Handball gained a lot of interest by researchers all over the world. The problem of the research lies in weakness in performing some shooting skill in handball. The researcher used the experimental method. The subjects were (19) sophomore students of physical education and sport sciences college/ University of Baghdad of the academic year 2015 – 2016. The research aimed at identifying the effect of these exercises using aids for teaching some types of shooting in handball. The researcher conclude the positive effects of the proposed exercises on some types of shooting. Finally the researcher recommended the necessity of using aids for teaching shooting in sophomore stuetns of physical edcaution and on other grades.